Transformasi modal sosial dalam digital society: Mendukung toleransi di Indonesia - S, Ahdan; Yahya, Muhammad; Kaharuddin, Kaharuddin; Arda, Arda; Sumandiyar, Adi; Baharuddin, Tawakkal (The Journal of Society and Media, 2024)
This study aims to cover the transformation of social capital in a digital society and its support for tolerance. This study used a quantitative method with descriptive content analysis. The research subjects are Twitter social media users. The object of this research is identified through user involvement in tolerance issues on social networks such as Twitter. The analysis tool that is maximized is Nvivo 12 Plus. The study reveals that disseminating harmful and intolerant content on social media platforms can pose a significant obstacle to establishing meaningful social connections. Such content is capable of provoking conflicts, reinforcing intergroup divisions, and eroding the social trust needed to foster tolerance. Fake news and negative narratives can reinforce negative stereotypes and have a significant impact on society's mindset. Promoting positive social values requires increasing digital literacy, taking a strong stance against content intolerance, implementing policies that promote tolerance, and ensuring access to information for all. This study highlights the grave danger of spreading harmful content on social media platforms like Twitter, as it can significantly threaten the building of substantial social capital. To promote digital tolerance, we need to increase literacy, enforce strict policies, strengthen online networks, and promote constructive dialogue